Identification and analysis of two sequences encoding ice-binding proteins obtained from a putative bacterial symbiont of the psychrophilic Antarctic ciliate Euplotes focardii. Issue 5 (14th February 2014) - Pucciarelli, Sandra; Chiappori, Federica; Devaraj, Raghul Rajan; Yang, Guang; Yu, Ting; Ballarini, Patrizia; Miceli, Cristina
Abstract We identified two ice-binding protein (IBP) sequences, named EFsymbAFP and EFsymbIBP, from a putative bacterial symbiont of the Antarctic psychrophilic ciliate Euplotes focardii. EFsymbAFP is 57.43% identical to the antifreeze protein (AFP) from the Stigmatella aurantiaca strain DW4/3-1, which was isolated from the Victoria Valley lower glacier. EFsymbIBP is 53.38% identical to the IBP from the Flavobacteriaceae bacterium strain 3519-10, isolated from the glacial ice of Lake Vostok. EFsymbAFP and EFsymbIBP are 31.73% identical at the amino acid level and are organized in tandem on the bacterial chromosome. The relatively low sequence identity and the tandem organization, which appears unique to this symbiont, suggest an occurrence of horizontal gene transfer (HGT). Structurally, EFsymbAFP and EFsymbIBP are similar to the AFPs from the snow mould fungus Typhula ishikariensis and from the Arctic yeast Leucosporidium sp. AY30. A phylogenetic analysis showed that EFsymbAFP and EFsymbIBP cluster principally with the IBP sequences from other Antarctic bacteria, supporting the view that these sequences belong to an Antarctic symbiontic bacterium of E. focardii. These results confirm that IBPs have a complex evolutionary history, which includes HGT events, most probably due to the demands of the environment and the need for rapid adaptation.